A case of partial xanthism in a marblefish Aplodactylus punctatus (Teleostei: Aplodactylidae) from southern Peru - Béarez, Philippe (2006)
A yellow skinned jerguilla (Aplodactylus punctatus) is reported for the first time from Ilo, Southern Peru. This condition of skin, in which yellow coloration predominates is called xanthism. This unique record probably corresponds to a range extension to the north of the «jerguilla reina», known along the central Chile coast.